A glioneuronal tumor with neurocytic rosettes harboring FGFR1 internal tandem duplication - A report of a unique case - Soukup, Jiri; Hajkova, Nikola; Hajkova, Veronika; Svajdler, Marian; Netuka, David; Majovsky, Martin (Neuropathology, 2025)
Rosette-forming glioneuronal tumors (RGNTs) with FGFR1 tyrosine kinase domain internal tandem duplication (FGFR1 ITD) is exceedingly rare, with only a few cases reported in the literature. Hereby we present a case of a tumor with RGNT morphology occurring in area of septum pellucidum of 43-year-old male. The tumor showed FGFR1 ITD, no PIK3CA, PIK3R1 or NF1 alterations and inconclusive methylation profile with match for class of "low-grade glial/glioneuronal/neuroepithelial tumors". No areas characteristic of dysembryoplastic neuroepithelial tumor were identified. A brief review of literature on discrepancies between morphological diagnosis of RGNT and molecular profile of the entity is provided.
Keywords: Brain Neoplasms; Male; glioneuronal tumors; neuroepitelové nádory; tandemové repetitivní sekvence; Receptor, Fibroblast Growth Factor, Type 1; nádory mozku; Adult; dospělí; mužské pohlaví; dysembryoplastic neuroepithelial tumor; Rosette forming glioneuronal tumor; receptor fibroblastových růstových faktorů, typ 1; pilocytic astrocytoma; FGFR; lidé; Tandem Repeat Sequences; Humans; Neoplasms, Neuroepithelial